PSYCHOLOGICAL PECULIARITIES OF YOUNGER SCHOOLCHILDREN IN DIFFERENT HEALTH GROUPS - N.V. Polyashova; A.G. Solov'ev; I.A. Novikova ("Paediatrician" Publishers LLC, 2008)
104 schoolchildren, studying in 1-4 forms of Arkhangelsk school were examined for the purpose of estimation of psychological peculiarities of younger children in different health groups. differentiation between health groups and psychological methods (Kettell's multiple factor personality question naire, method «house tree human», and index of psychological wellbeing) were used. Younger school children, relative to health group had such qualities as openness, benevolence, commutability, obedience, pliability, honesty, observance. Children from II health group had distinct forming of intellectual functions, independence, forcefulness, composure, they were optimists. School children from III and IV health groups had distinct disorders of psychological adaptation, apparent in difficulties of interpersonal communication, increased uneasiness, and sense of inferiority, hostility and propensity to conflicts, what was related with their functional disorders.Key words: psychological peculiarities, health groups, younger school children.